Evaluación de rendimientos para queso fresco a partir de leche cruda fluida procedente de tres razas de ganado vacuno lechero - Espinosa Rosales, Franklin Rodrigo (2015)
This thesis called "EVALUATION OF PERFORMANCE FOR FRESH CHEESE BASED ON RAW MILK FLUID FROM THREE RACES OF DAIRY CATTLE" Performance evaluation was conducted on milk was bought from three different breeds of dairy herds in the province of Loja, namely Holstein Friesian, Holstein Mixed and Brown Swiss in order to determine the best yield, the physicochemical analysis of each and presence of somatic cells. Nine repetitions for each race was carried out on approximately 15 liters of raw milk, thus totaling 405 liters from the three races between the months of November 12th to January 12th. The different cheese manufacturing processes and the analysis of the samples were carried out at the Dairy Processing Pilot Plant at the National University of Loja. From the physical-chemical analysis it was found that the milk from the Brown Swiss breed displayed better results. As for the variable rate of return we obtained the following results: the Brown Swiss breed exhibited the highest performance with 2.20 kg of cheese representing 14.12%, followed by the Holstein Mixed breed with 2.17 kg representing 13.39% and finally the Holstein Friesian breed with 1.9 kg representing 13%. All these amounts were the result of the nine milk repetitions carried out on each race. With respect to the somatic cells, nine samples were collected from each race from the various repetitions giving the following result: the Brown Swiss exhibited the least amount of somatic cells resulting in no positive sample, this was followed by the Holstein Friesian that presented three positive samples and finally the Holstein Mixed that exhibited six positive samples.